1990
DOI: 10.3354/meps062259
|View full text |Cite
|
Sign up to set email alerts
|

Biomagnification of mercury in a marine grazing food-chain: algal cells Phaeodactylum tricornutum, mussels Mytilus edulis and flounders Platichthys flesus studied by means of a stepwise-reduction-CVAA method

Abstract: A stepwise-reduction-cold vapor atomic absorption spectrometry (CVAA) method has been further developed. The method is relatively simple and quick and allows measurements of both inorganic and organic mercury in the same small biological sample. It provides an effective technique for studying biomagnification of mercury in a marine grazing food-chain (algae/mussels/fish). In laboratory experiments with mussels exposed to both inorganic mercury (965 ng I-') and organic mercury (methylmercury) (35 ng I-'), and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0
5

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 18 publications
6
44
0
5
Order By: Relevance
“…This implies potential effects on the food web of the surrounding area as already reported by several authors studying marine systems (Riisgard and Hansen, 1990;Futter, 1994;Jarman et al, 1996;Atwell et al, 1998). This hypothesis is supported by the high mean HgT concentrations measured in pelagic species caught outside the bay, which are similar to those reported for other sites affected by Hg pollution: the Adriatic Sea (Wolfgang, 1983;Storelli and Marcotrigiano, 2001;Storelli et al, 2002Storelli et al, , 2004Storelli et al, , 2007Storelli et al, , 2010Gibičar et al, 2009), Turkish areas (Tuzen, 2009), Spanish coastal areas (Pastor et al, 1994) and Israel area (Hornung et al, 1980) (Table 2).…”
Section: Sources Of Hgt and Fish Contamination In Augusta Baysupporting
confidence: 84%
“…This implies potential effects on the food web of the surrounding area as already reported by several authors studying marine systems (Riisgard and Hansen, 1990;Futter, 1994;Jarman et al, 1996;Atwell et al, 1998). This hypothesis is supported by the high mean HgT concentrations measured in pelagic species caught outside the bay, which are similar to those reported for other sites affected by Hg pollution: the Adriatic Sea (Wolfgang, 1983;Storelli and Marcotrigiano, 2001;Storelli et al, 2002Storelli et al, , 2004Storelli et al, , 2007Storelli et al, , 2010Gibičar et al, 2009), Turkish areas (Tuzen, 2009), Spanish coastal areas (Pastor et al, 1994) and Israel area (Hornung et al, 1980) (Table 2).…”
Section: Sources Of Hgt and Fish Contamination In Augusta Baysupporting
confidence: 84%
“…In contrast, no Hg(II) was found in the head after 28 d elimination. Riisgaard & Hansen (1990) showed that flounder Platichthys flesus force-fed with contaminated mussels accumulated MeHg in blood cells, liver, kidney and muscle tissues, while Hg(II) only accumulated in measurable amounts in the liver and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no Hg(II) was found in the head after 28 d elimination. Riisgaard & Hansen (1990) showed that flounder Platichthys flesus force-fed with contaminated mussels accumulated MeHg in blood cells, liver, kidney and muscle tissues, while Hg(II) only accumulated in measurable amounts in the liver and kidney.We used the radiotracer technique to study the biokinetics of Hg(II) and MeHg in the sweetlips. Whether there was any biotransformation (methylation and demethylation) within the fish body was not revealed by our study.…”
mentioning
confidence: 99%
“…Mercury (Hg) is a non-essential heavy metal that biomagnifies within food webs (Riisgard & Hansen 1990, Jarman et al 1996 and can accumulate in toxic concentrations in top predators (Eisler 1987). Although high levels of exposure are often associated with localised sources of pollution (such as chlor-alkali works or lignite burning), elevated concentrations have also been reported in biota from high latitudes (Wagemann et al 1990, Bocher et al 2003.…”
Section: Introductionmentioning
confidence: 99%